MODELLING OF PERIODIC ECONOMIC PROCESSES - Циганчук , Роман (Socio-economic relations in the digital society, 2019)
The model of an equation of prices on asset level is investigated. Mathematical modelling and computer simulation of periodic economic processes discrete in time are considered. The methodology of replacement of the differential equations is described. The decision and the analysis are made in two numerous ways: by the method of uncertain coefficients and solution of a boundary problem. In economic dynamics, continuous and discrete time is used. The continuous time is convenient for simulation as allows using the device of differential calculus and differential equations. The discrete time is convenient for the handling of applied problems whereas the statistical data is always discrete and belong to the specific units of time. For the discrete time, the device of the diff erence equations is used. By the way, the familiar models of economic dynamics exist both in the continuous and in the discrete options. In both cases, they have approximately identical accuracy and level of complexity of models is almost the same.